Estudo da Memória Autobiográfica na Perturbação Bipolar - Bobrowicz-Campos, E. (2015)
Background: It has been widely established that clinical depression and posttraumatic stress disorder are associated with a difficulty in accessing specific autobiographical information. Apparently, this condition contributes to the onset and persistence of these disorders, as well as to poor prognosis. Concerning to the mechanisms underlying the phenomenon of overgeneral memory, there are still some critical issues that remain unclear. Recent studies demonstrated that reduced specificity in autobiographical memory (AM) is also related to the bipolar disorder (BD). Objectives: The principal aim of this project was to investigate the mechanism of overgeneral memory across different states of BD and explore its associations with neuropsychological performance, mood and psychopathological symptoms. Furthermore, we examined strategies that are used by euthymic BD patients during the encoding and the retrieval of emotional information in the context of lifelike events. Method: In study 1, 71 BD patients (25 clinically stable, 23 in a hypomanic state and 23 in a depressive state) and 26 healthy controls responded to the Portuguese version of the Autobiographical Memory Test (AMT) (adapted by the author of this dissertation). In study 2, 14 remitted BD patients and 23 healthy controls performed an experimental task based on virtual reality and completed a questionnaire for assessing encoding and retrieval strategies. All participants were also examined using a neuropsychological battery. In addition, they completed self-rated measures assessing mood and psychopathological symptoms. Results: In study 1, depressive and hippomanic BD patients reported less specific AMs than healthy individuals. Depressive patients failed to provide specific AMs to all kinds of cues (positive, negative and neutral valences). Hippomanic patients manifested more retrieval difficulties on the presence of positive and neutral cues. However, their normal scoring in negative condition was partly due to repeated memories. Remitted patients showed biased retrieval only when it was applied a response time limit. In study 2, compared to healthy controls, remitted BD patients recognized more information associated with negative lifelike events and showed difficulty in the retrieval information related to positive lifelike events. Conclusion: Findings from study 1 indicate that separate psychological processes are implicated in BD remission, depression and mania, but changes in AM retrieval are evident in all phases of this illness. Findings from study 2 suggest that changes on processing of emotional information, specific to remitted BD patients, are caused by unsuccessful consolidation of positive data on the autobiographical knowledge and by activation of maladaptive emotional regulation processes.